2018
DOI: 10.5562/cca3396
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Flame Retardant Polyurethane Prepared with Epoxidized Soybean Oil and Vinylphosphonic Acid

Abstract: The synthesis of novel polyol was carried out by the reaction of epoxidized soy-bean oil (ESBO) throught ring opening reaction with vinyl phosphonic acid (VPA) bearing two functional groups, vinyl and phosphonic acid. The synthesized polyol (PolP) and 4,4´-methylenebis(phenyl isocyanate) (MDI) were reacted to prepare biobased and inherently flame retardant polyurethane foam (PPPU). FTIR, 1 H, 13 C and 31 P NMR spectroscopy confirmed that the epoxy ring of ESBO was opened by phosphonic acid group of VPA, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…A new band is observed in Figure 4(b) at 802 cm −1 Which corresponds to epoxy groups thus confirming the successful epoxidation to chaulmoogra oil. 47
Figure 5.FTIR spectrum of (a) chaulmoogra oil (CMO) (b) epoxidised chaulmoogra oil (c) polyol derived from CMO, (d) grape seed oil (GSO) (e) epoxidised grape seed oil (f) polyol derived from GSO. H 1 -NMR Analysis of Chaulmoogra oil and Chaulmoogra polyol.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new band is observed in Figure 4(b) at 802 cm −1 Which corresponds to epoxy groups thus confirming the successful epoxidation to chaulmoogra oil. 47
Figure 5.FTIR spectrum of (a) chaulmoogra oil (CMO) (b) epoxidised chaulmoogra oil (c) polyol derived from CMO, (d) grape seed oil (GSO) (e) epoxidised grape seed oil (f) polyol derived from GSO. H 1 -NMR Analysis of Chaulmoogra oil and Chaulmoogra polyol.
…”
Section: Resultsmentioning
confidence: 99%
“…A new band is observed in Figure 4(b) at 802 cm À1 Which corresponds to epoxy groups thus confirming the successful epoxidation to chaulmoogra oil. 47 FTIR spectra of the polyol derived from chaulmoogra oil (Figure 5(c)) shows a band at 3495 cm À1 corresponding to -OH (broad stretching) which indicates the formation of polyol from the epoxidised chaulmoogra oil. Disappearance of band at 2983 cm À1 corresponding to =CH group of double bonds of chaulmoogra oil and epoxidised chaulmoogra oil indicates it's conversion into hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, according to the authors, the flame retardant acted in both gas and condensed phases. Özşeker et al [98] synthesized a novel bio-based polyol containing phosphorus through a ring-opening reaction of epoxidized soybean oil (ESBO) and vinyl phosphonic acid (VPA). The authors only reported the LOI test and mentioned that the LOI value of flame-retardant PU was 26.4.…”
Section: Type Of Pumentioning
confidence: 99%
“…23 Similarly, vinyl phosphonic acid was used to synthesize soybean oil-based polyols, and the obtained polyurethane had an LOI value of 26.4%. 24 A biobased flame-retardant plasticizer was synthesized from epoxidized soybean oil (ESO) and 9,10-dihydro-9oxa-10-phosphaphenanthrene 10-oxide for polyvinyl chloride (PVC), and the plasticized PVC achieved a high LOI value of 36.3%. 25 However, the developed VO polymers exhibit low biobased contents and are difficult to be recycled after the end of service due to the incorporation of FRs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, diethyl phosphate was used to react with epoxidized castor oil for preparing flame-retardant polyurethane foam with an LOI value of 24.3% . Similarly, vinyl phosphonic acid was used to synthesize soybean oil-based polyols, and the obtained polyurethane had an LOI value of 26.4% . A biobased flame-retardant plasticizer was synthesized from epoxidized soybean oil (ESO) and 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide for polyvinyl chloride (PVC), and the plasticized PVC achieved a high LOI value of 36.3% .…”
Section: Introductionmentioning
confidence: 99%